2017
DOI: 10.1186/s12936-017-1770-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular surveillance of drug resistant vivax malaria in Myanmar (2009–2016)

Abstract: BackgroundOne of the major challenges for control and elimination of malaria is ongoing spread and emergence of drug resistance. While epidemiology and surveillance of the drug resistance in falciparum malaria is being explored globally, there are few studies on drug resistance vivax malaria.MethodsTo assess the spread of drug-resistant vivax malaria in Myanmar, a multisite, prospective, longitudinal study with retrospective analysis of previous therapeutic efficacy studies, was conducted. A total of 906 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
47
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 18 publications
14
47
6
Order By: Relevance
“…The increased rate of these mutations suggests that chloroquine resistance in P. vivax will become more common in the South Asia region where chloroquine has remained the first-line drug [39]. Our findings from clinical isolates from Southeast Asia were also similar to other studies in this location [5][6][7]16,40]. A clinical report of chloroquine-resistant P. vivax in a Thai pregnant woman indicated that recurrent parasites during Day 21 and 143 carried the double F976:L1076 mutation [40].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The increased rate of these mutations suggests that chloroquine resistance in P. vivax will become more common in the South Asia region where chloroquine has remained the first-line drug [39]. Our findings from clinical isolates from Southeast Asia were also similar to other studies in this location [5][6][7]16,40]. A clinical report of chloroquine-resistant P. vivax in a Thai pregnant woman indicated that recurrent parasites during Day 21 and 143 carried the double F976:L1076 mutation [40].…”
Section: Discussionsupporting
confidence: 87%
“…This double mutation was found in Thailand in 2008 (49.2%) and again in 2014 (18.4%) [7]. The same double mutations were found in 15.4% of samples in Myanmar between 2009 and 2016 [5]. This could indicate that chloroquine-resistant P. vivax is not only present in Thailand but also in neighbouring Myanmar.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations